'A dreadful phenomenon described and improved': Reverend John Fletcher's account of the Buildwas earthquake of 1773. (April 2019) - Bowen, James P.; Macdonald, Neil
Abstract: Earthquakes are of interest to geologists and physical geographers, yet rarely attract historical geographers' attention. This paper uses contrasting representations of the Buildwas, Shropshire, 'earthquake' of 1773 to reconstruct the course of the event and its immediate aftermath. The contemporary mapping of the scene records the changes in the physical landscape, with the hillside slippage blocking the River Severn, a vital inland navigation route, forcing a new channel to be cut. This paper examines the role of Reverend John Fletcher, a prominent theologian and leading figure in the Methodist movement, who preached on the site immediately following the event drawing Biblical parallels from a providentialist perspective. However, Fletcher was the epitome of an eighteenth-century 'clerical naturalist' and his account provides equal attention to the moral and physical causes of the event, including numerous personal testimonies. Reviewing the evidence and its interpretation, this paper questions why contemporaries who debated the precise causes referred to it as an 'earthquake', or alternatively a landslip, contextualising their discussions in the wider intellectual movement of the Enlightenment and debates about the relationship between 'science' and 'religion'. It shows how this local event was compared with other well documented earthquakes at London and Lisbon in 1750 and 1755 respectively, influencing how contemporaries understood what happened at Buildwas. Furthermore, our analysis indicates that it was not an 'earthquake', but rather a landslip following a period of prolonged precipitation combined with high river levels which probably undermined the slope. Highlights: Analyses contemporary descriptions of the earthquake at Buildwas, Shropshire, 27 May 1773. Examines the contribution of Reverend John Fletcher (1729–1785) to eighteenth-century provincial science. Interprets the event within prevailing religious and scientific understanding of earthquakes. Highlights the interchangeable use of the terms earthquake and landslip in the eighteenth century. Contributes to scholarship on the provincial clergy naturalist and providentialism.